Adverse Effects of COVID-19 on Perinatal Outcomes Globally. Issue 2 (March 2022) - Callister, Lynn Clark
Abstract : The COVID-19 pandemic has adversely affected outcomes for childbearing women and their babies around the globe, especially in low resource, low-to-middle income countries. Our global health and nursing expert, Dr. Callister, reviews some of the most recently published articles on the impact of COVID-19 on this vulnerable population.